Arbeitsgemeinschaft Heidelberg-Göttingen: 5.7. bis 7.7. 1969 - Roquette, Peter (Tagungsbericht, 1969)
Arason, Göttingen; Frey, Heidelberg; Geyer, Heidelberg; H. Göhner, Heidelberg; U. Göhner, Tübingen; Hahnel, Bonn; Herrmann, Heidelberg; Kneser, Göttingen; Lange, Göttingen; Leicht, Heidelberg; Lipman, Purdue; Lorenz, Konstanz; Maus, Göttingen; Pfeuffer, Göttingen; Popp, Heidelberg; Radbruch, Tübingen; Reiter, Göttingen; Ritter, Heidelberg; Roquette, Heidelberg; Tamme, Göttingen